Active smoking and risk of estrogen receptor positive and triple-negative breast cancer among women 20–44 years of age - Kawai, Masaaki (2014)
BACKGROUND: The evidence regarding the relationship between smoking and breast cancer among young women is mixed, and prior studies have not assessed if smoking is differentially associated with risks of the major breast cancer subtypes. METHODS: We conducted a population-based case-control study consisting of 778 estrogen receptor positive (ER+) and 182 triple-negative (TN) invasive breast cancer cases 20-44 years of age diagnosed from 2004-2010 in the Seattle-Puget Sound metropolitan area, and 938 cancer-free controls. We assessed associations between various aspects of smoking history and risks of ER+ and TN breast cancer using polytomous logistic regression. RESULTS: Ever smokers had a 1.3-fold [95% confidence interval (CI): 1.1-1.7] increased risk of breast cancer overall, and when stratified by cancer subtype they had a 1.4-fold (95% CI: 1.1-1.8) increased risk of ER+ breast cancer but no elevation in their risk of TN disease [odds ratio (OR) = 1.1, 95% CI: 0.7-1.6]. Current/recent smokers with a ≥10 pack-year history of smoking had a 1.6-fold (95% CI: 1.1-2.4) increased risk of ER+ breast cancer, but no increase in their risk of TN breast cancer (OR=1.0, 95% CI: 0.5-1.9). CONCLUSIONS: Our results suggest that young women who are current/recent smokers with high pack-year histories may have an increased risk of ER+, but not TN, breast cancer. While this association is modest, our findings suggest that an increased risk of ER+ breast cancer may be another health risk incurred by young women who smoke.